2013
DOI: 10.1002/mus.23759
|View full text |Cite
|
Sign up to set email alerts
|

An open trial of long‐term testosterone suppression in spinal and bulbar muscular atrophy

Abstract: Leuprorelin was not effective in this small long-term treatment trial in SBMA. The possibility that earlier treatment might be beneficial may deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…While these clinical trials identified potentially beneficial outcomes from reducing AR activation (Fernandez-Rhodes et al, 2011; Katsuno et al, 2010), the global reduction in AR function can have deleterious effects on the mental well-being of patients (Fernandez-Rhodes et al, 2011). Moreover, in recent clinical trials (Rhodes et al, 2009; Yamamoto et al, 2013), the observed correlation between muscle strength and testosterone levels suggests that the anabolic effects of AR function in muscle should be considered in the development of effective therapies for SBMA.…”
Section: Discussionmentioning
confidence: 99%
“…While these clinical trials identified potentially beneficial outcomes from reducing AR activation (Fernandez-Rhodes et al, 2011; Katsuno et al, 2010), the global reduction in AR function can have deleterious effects on the mental well-being of patients (Fernandez-Rhodes et al, 2011). Moreover, in recent clinical trials (Rhodes et al, 2009; Yamamoto et al, 2013), the observed correlation between muscle strength and testosterone levels suggests that the anabolic effects of AR function in muscle should be considered in the development of effective therapies for SBMA.…”
Section: Discussionmentioning
confidence: 99%
“…A key factor contributing to the toxic GOF of polyQ-AR is the deposition of the disease protein into micro-aggregates and inclusion bodies, and specific types of polyQ-AR-positive aggregates have been linked to neurotoxicity in vitro and in vivo (12,(16)(17)(18)(19). Although the androgen-dependent nature of disease and experimental evidence support chemical and physical castration as a therapeutic strategy for SBMA (10,11,13), clinical trials based on this approach showed benefits limited to a subset of patients (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…It also should be pointed out that an open-label study with leuprorelin in 16 patients with SBMA demonstrated no improvement in muscle weakness 12. It is suspected that lack of androgens may cause muscle weakness and may even facilitate further neuronal degeneration 13.…”
Section: No Testosterone For Spinal and Bulbar Muscular Atrophy (Sbma)mentioning
confidence: 99%